Implementasi Ideologi Terbuka Pancasila Pada Pemberdayaan Perempuan Berbasis Keterampilan Budidaya Tanaman Hidroponik - Desmawati, Liliek; K, Khusni; Sandi, Akbar Dwi Febiali; Jannah, Helmina Zahrotul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Empowering women through hydroponic cultivation skills is an important strategy to overcome gender inequality and improve welfare in Jurangagung Village. Pancasila, as the Indonesian state ideology, provides a philosophical basis that is relevant to the principles of social justice and fair humanity. The implementation of Pancasila principles in the hydroponics program aims to increase women's participation, overcome challenges such as limited access to education, and maximize economic and social benefits. This program includes skills training, careful planning, pest control, and use of technology. This strategy is expected to strengthen the role of women in the local economy, increase food security, and support sustainable development in villages. The application of the Pancasila ideology will strengthen the success of the program and support community welfare.